Microbial selenium nanoparticles (SeNPs) and their application as a sensitive hydrogen peroxide biosensor - Prasad, Kumar Suranjit; Vaghasiya, Jayraj V.; Soni, Saurabh S.; Patel, Jitesh; Patel, Rinkesh; Kumari, Madhu; Jasmani, Falguni; Selvaraj, Kaliaperumal (Applied Biochemistry and Biotechnology, 2015)
The cell-free extract, a crude enzyme (cytosolic and membrane fraction) obtained from an environmental isolate, Bacillus pumilus sp. BAB-3706 worked as excellent in reducing as well as stabilizing agent and facilitated the formation of stable colloidal selenium nanoparticles (SeNPs). Resulting nanoparticles were characterized using UV-vis spectrophotometer, TEM, EDAX, FT-IR and XRD, respectively. A working electrode was modified by coating the surface of indium tin oxide (ITO) with colloidal SeNPs. Successive additions of H2O2 (100 to 600 mu M) in conventional three electrodes system, cyclic voltammeter with potential scan rate 25.0 mV/s, in 0.1 M phosphate buffer solution (PBS) yielded increase in current. A perpetual amperometric response at fixed potential (-1.0 V) and at selected time interval of 100 s showed different magnitude of current at every addition of H2O2. The linear range of detection of H2O2 was from 5 to 600 mM (R (2) = 0.9965), while the calculated limit of detection was found to be 3.00 mu M. The current study suggested that microbial SeNPs can be used for fabrication of low cost, sensitive H2O2 biosensor.
Keywords: Biosensor; EDAX; Hydrogen peroxide; Selenium nanoparticles; TEM; UV-vis spectroscopy

Synthesis of water soluble CdS nanoparticles and study of their DNA damage activity - Prasad, K. S.; Amin, T.; Katuva, S.; Kumari, Madhu; Selvaraj, Kaliaperumal (Arabian Journal of Chemistry, 2017)
This study reports a novel method for preparation of water soluble CdS nanoparticles using leaf extract of a plant, Asparagus racemosus. The extract of the leaf tissue which worked as a stabilizing and capping agent, assisted the formation of nanoparticles. Nanoparticles were characterized using a UV–vis spectrophotometer, Photoluminescence, TEM, EDAX, XRD and FT-IR. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, CdS of diameter ranging from 2 to 8 nm. X-ray diffraction studies showed the formation of 1 1 1, 2 2 0 and 3 1 1 planes of face-centered cubic (fcc) CdS. EDAX analysis confirmed the presence of Cd and S in nanosphere. The cytotoxicity test using MTT assay as well as DNA damage analysis using comet assay revealed that synthesized nano CdS quantum dots (QDs) caused less DNA damage and cell death of lymphocytes than pure CdS nanoparticles.

Removal of fluoride from aqueous solution by mesoporous silica nanoparticles functionalized with chitosan derived from mushroom - Srivastava, Anushree; Kumari, Madhu; Ramanathan, Alagappan; Selvaraj, Kaliaperumal; Prasad, Bablu; Prasad, Kumar Suranjit (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
In the present study, chitosan functionalized mesoporous silica nanoparticles have been synthesized. Chitosan derived from an edible mushroom, Agaricus bisporus was used during synthesis of chitosan functionalized silica nanoparticles. The functionalized silica nanoparticles were subjected to fluoride sorption using a batch method which subsequently showed removal efficiency of 95% with maximum sorption capacity, 58.8 mg/g. The characterization of nanoparticles was carried out by SEM, EDAX, XRD and FTIR analysis respectively. EDAX analysis suggested that oxygen, 51.83% and silica 37.24% was main constituent of the functionalized nanomaterials. XRD yielded characteristic diffraction pattern corresponding to the lattice planes (100), (110), (112), (120), (200) and (220) respectively. Sorption data was used to study equilibrium isotherm namely Langmuir and Freundlich model. The adsorption capacity increased with temperature while kinetics studies revealed that the adsorption process followed a pseudo-second-order rate equation. The enthalpy change (Delta H) and entropy change (Delta S) was found to be -31.36 kJmol(-1) and -7.75 Jmol(-1) K-1, showing endothermic and spontaneous nature of the fluoride adsorption. Data suggested that the nature of adsorption belonged to chemisorptions. The overall results suggested that the synthesized nanoparticles showed strong and specific affinity for fluoride and could be excellent adsorbents for defluoridation.
Keywords: Adsorption; Chitosan; EDAX; Fluoride; SEM